2011
DOI: 10.3109/17435390.2011.587904
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of enzyme activity by nanomaterials: Potential mechanisms and implications for nanotoxicity testing

Abstract: The objective of this study was to investigate whether nanoparticle-exposure affects enzyme function and to determine the mechanisms responsible. Silicon, Au, and CdSe nanoparticles were synthesized in house and their physicochemical properties were characterized. The activity of purified lactate dehydrogenase (LDH) was inhibited or abolished by all nanoparticles tested. Inhibition was dependent upon particle core and surface-functional group composition. Inhibition of LDH was absent in crude tissue homogenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 34 publications
4
76
0
Order By: Relevance
“…The implications could be significant if vital circulatory proteins, such as immunoglobulins (e.g., IgE, IgG), form part of the NP‐protein corona and are prevented from executing their biological roles. For example, we have previously demonstrated that lactate dehydrogenase (LDH) activity decreases when exposed to metal NPs by altering the conformational structure of the protein 5, 7. If animals are exposed to PAA‐based materials either directly as a therapeutic or inadvertently through environmental exposure, this may result in diminution of the functional activity of IgE mediated responses, and thereby impede the activation of immune function and alteration of their antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications could be significant if vital circulatory proteins, such as immunoglobulins (e.g., IgE, IgG), form part of the NP‐protein corona and are prevented from executing their biological roles. For example, we have previously demonstrated that lactate dehydrogenase (LDH) activity decreases when exposed to metal NPs by altering the conformational structure of the protein 5, 7. If animals are exposed to PAA‐based materials either directly as a therapeutic or inadvertently through environmental exposure, this may result in diminution of the functional activity of IgE mediated responses, and thereby impede the activation of immune function and alteration of their antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…The propensity for NPs to bind and alter the conformational structure and biological function of proteins,5, 7 suggests that they may also alter the function of surface membrane receptors, including FcεRIs. Huang et al20 showed that DNP‐albumin labeled gold NPs directly stimulated FcεRI‐mediated responses by providing cross‐linking of receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of protein, mostly BSA, could prevent interference, but it also could increase it. While false-negative results by the inhibition of LDH activity by Si, Au, and CdSe NPs 96 was avoided, the addition of BSA caused false-negative effects in protein detection via the Bradford reagent. 97 For the identification of potential assay interference, the incubation of NPs with the assay compounds alone (in the absence of cells) and with cells alone (in the absence of assay compounds) can be used.…”
Section: In Vitro -Assay Interferencementioning
confidence: 99%
“…[108] Consequently, assays that measure enzymatic activity are likely to be affected by NMs. For example, the presence of active LDH in test media is often used as an indicator of cell death following its release into the media.…”
Section: Optical Interferencementioning
confidence: 99%
“…of substrates and inactivation of enzymes. Assays affected include, MTT, [89] PI (propidium iodide), [104] LDH, [108] alamar blue and neutral red. [81,82] (c) Catalytic properties of NMs and their generation of reactive oxygen species (ROS) in assay mixtures can generate false positives by oxidising non-fluorescent probes to fluorescent probes, such as 2 0 ,7 0 -dichlorodihydrofluorescin diacetate (DCFH-DA) to DCF.…”
Section: Optical Interferencementioning
confidence: 99%